Telecommunication service quality analysis using integration of SIPA and modified Kano - Hanny Kanavika Rizky Munawar; Annisa Kesy Garside; Adhi Nugraha; Amelia Khoidir (Jurnal Sistem dan Manajemen Industri, 2023)
This article investigates the integrated approach of the Simultaneous Importance-Performance Analysis (SIPA) model and the modified Kano model to evaluate and prioritize service attributes for telecommunication companies in Indonesia. The study is based on the demographic profiles and usage patterns of 74 respondents. The results demonstrate that the SIPA and Kano models can provide valuable insights for identifying priority areas and effective strategies for improving service quality. Specifically, the SIPA model helps to compare competitor performance and identify important service attributes. In contrast, the modified Kano model facilitates a dynamic cycle of service attribute evaluation to inform managerial strategies. This article contributes by highlighting the potential of the proposed approach to offer valuable insights to telecommunication companies seeking to enhance their service offerings and remain competitive in a constantly evolving market.